Pravastatin-Induced Acute Pancreatitis: A Case Report and Literature Review - Zahid Ijaz Tarar MD; Muhammad Usman Zafar MD; Ghulam Ghous MD; Umer Farooq MD; Hafiz Muhammad Hassan Shoukat MD (SAGE Publishing, 2021)
Pancreatitis is inflammation of pancreas associated most commonly with chronic alcoholism and gallstones. Other less common causes of pancreatitis are hyperlipidemia, infections, surgery, trauma, post endoscopic retrograde cholangiopancreatography, and drugs. Drugs are now increasingly recognized as a cause of pancreatitis, and high suspicion and exclusion of other most common causes is required before considering drug-induced pancreatitis. There are few case reports of acute pancreatitis in the literature after statin use, but out of these, only 3 are after starting pravastatin. We are reporting a case of 49-year-old male who presented with nausea, vomiting, and abdominal pain. His laboratory findings were significant for lipase more than 10 000 on admission, and computed tomography scan of abdomen was showing peripancreatic fat stranding and inflammation. After exclusion of most common causes of pancreatitis, pravastatin was found probable culprit for his symptoms, which he started taking 2 weeks ago. We also reviewed the literature on statins-induced acute pancreatitis. With increased uses of statins, physician need to be vigilant to suspect statins as a culprit in cases of pancreatitis with unknown etiology. Prompt discontinuation of statins is required in these cases.